The sum of Doris and Fred's ages is y . Doris is 12 years : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 20 Jan 2017, 10:55

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# The sum of Doris and Fred's ages is y . Doris is 12 years

Author Message
Intern
Joined: 16 Sep 2006
Posts: 22
Followers: 0

Kudos [?]: 0 [0], given: 0

The sum of Doris and Fred's ages is y . Doris is 12 years [#permalink]

### Show Tags

16 Sep 2006, 19:02
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

The sum of Doris and Fred's ages is y. Doris is 12 years older than Fred. How many years old will Fred be y years from now, in terms of y.
A. y-6
b. 2y-6
C. y/2-6
D. 3y/2-6
E. 5y/2-6

I have the answer by plugging in numbers, but can't figure out how this formula came about. Any help would be greatly appreciated. Thanks.
Manager
Joined: 23 Jul 2006
Posts: 50
Followers: 1

Kudos [?]: 1 [0], given: 0

### Show Tags

16 Sep 2006, 19:19
Hi.

You have:

D + F = Y

and you have that:

D = F + 12

If you replace the second equation in the first euation, we have:

2F + 12 = Y => F = (Y-12)/2

That is the FredÂ´s age today. In y more years will be: F + Y ==>

==> (Y-12)/2 + Y ==> (3/2)Y - 6 ..... (D)
_________________

Woody crack the GMAT

Intern
Joined: 16 Sep 2006
Posts: 22
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

16 Sep 2006, 19:29
Thank you, I can sleep now...
SVP
Joined: 05 Jul 2006
Posts: 1743
Followers: 6

Kudos [?]: 316 [0], given: 49

### Show Tags

17 Sep 2006, 01:56
The sum of Doris and Fred's ages is y. Doris is 12 years older than Fred. How many years old will Fred be y years from now, in terms of y.
A. y-6
b. 2y-6
C. y/2-6
D. 3y/2-6
E. 5y/2-6

D+F = Y BUT F+12 = D THUS 2F +12 = Y

F NOW = Y-12/2 , F Y YEARS FROM NOW = (Y-12)/2 +Y = 3y/2-6

Senior Manager
Joined: 20 Feb 2006
Posts: 373
Followers: 1

Kudos [?]: 25 [0], given: 0

### Show Tags

17 Sep 2006, 03:05
D) 3y/2 - 6

Same working as above
Intern
Joined: 17 Apr 2006
Posts: 42
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

17 Sep 2006, 10:11
axl169 wrote:
The sum of Doris and Fred's ages is y. Doris is 12 years older than Fred. How many years old will Fred be y years from now, in terms of y.
A. y-6
b. 2y-6
C. y/2-6
D. 3y/2-6
E. 5y/2-6

I have the answer by plugging in numbers, but can't figure out how this formula came about. Any help would be greatly appreciated. Thanks.

Ans: D

Here'z how:

d + f = y, and d = f + 12, (d and f are ages of Doris and Fred)

therefore: 2f + 12 = y or f = (y-12)/2 --- (1)

Fred's age, y years from now is f + 12
= y/2 -6 + y
= 3y/2 - 6
Senior Manager
Joined: 28 Aug 2006
Posts: 306
Followers: 13

Kudos [?]: 150 [0], given: 0

### Show Tags

17 Sep 2006, 20:08
axl169 wrote:
The sum of Doris and Fred's ages is y. Doris is 12 years older than Fred. How many years old will Fred be y years from now, in terms of y.
A. y-6
b. 2y-6
C. y/2-6
D. 3y/2-6
E. 5y/2-6

I have the answer by plugging in numbers, but can't figure out how this formula came about. Any help would be greatly appreciated. Thanks.

Folks, again different ways were given to answer this.
But where is our faster method i.e giving some values and then proceeding...

Let F=24 Clearly D = 36, this mean y=60
After y years ie after 60 years F= 24+60 = 84.

Go to options.........
Placing y=60 Option D gives us 84.
So it is D.........

I recommend all of u to get into these methods

Regards,
_________________

Last edited by cicerone on 25 Sep 2008, 00:25, edited 1 time in total.
Director
Joined: 28 Dec 2005
Posts: 755
Followers: 1

Kudos [?]: 14 [0], given: 0

### Show Tags

17 Sep 2006, 22:41
axl169 wrote:
The sum of Doris and Fred's ages is y. Doris is 12 years older than Fred. How many years old will Fred be y years from now, in terms of y.
A. y-6
b. 2y-6
C. y/2-6
D. 3y/2-6
E. 5y/2-6

I have the answer by plugging in numbers, but can't figure out how this formula came about. Any help would be greatly appreciated. Thanks.

d+f=y
d=f+2
=>2f+12=y
=>f = (y-12)/2
f+y = (y-12)/2+y = 3y/2 -6

D
Director
Joined: 06 Sep 2006
Posts: 743
Followers: 1

Kudos [?]: 36 [0], given: 0

### Show Tags

19 Sep 2006, 11:43
D + F = Y; D = 12 + F; => 12 + F + F = Y => 2F = Y - 12

=> F = (Y - 12)/2

After Y years:
F = (Y - 12)/2 + Y => (Y -12 + 2Y)/2 => (3Y - 12)/2

=> 3Y/2 - 6. So D is my choice.
19 Sep 2006, 11:43
Display posts from previous: Sort by